WANITA MULIA DALAM AL-QUR’AN: TAFSIR TEMATIK SURAT MARYAM - Irfan Rizky Maulana (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2025)
The story of Maryam in Surah Maryam is an important narrative in the Qur'an that holds many wisdom and lessons for modern life. This research aims to analyze Maryam's values of chastity, piety, patience, and spiritual strength and its relevance to women's spirituality, education, and empowerment. This research uses a qualitative method with content analysis based on authoritative interpretations and related literature. The results of the study show that Maryam's story illustrates piety, sincerity in accepting destiny, and spiritual strength in facing trials, as well as providing important lessons about dealing with change, social stigma, and strengthening the role of women in various aspects of life. This story also affirms God's love for His servants through the guidance, help, and miracles provided. The study concludes that Maryam's story offers a universal example for building faith, character, and courage in everyday life.